Equilibrium electrochemical synthesis diagrams of systems, forming homogeneous alloys and compounds - Kaptay G. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In the present paper thermodynamic limitations will be derived and summarized in the form of Equilibrium Electrochemical Synthesis (EES) diagrams, in order to predict the composition of the equilibrium phase, synthesized by galvanostatic co-deposition of components on inert electrodes. As a thermodynamic parameter, a difference of deposition potentials of pure components ( ∆E) on inert cathodes is used (this parameter is a function of melt composition and temperature). Generally, the EES diagram predicts the equilibrium composition of the alloy as function temperature and ∆E. However, for systems with homogeneous alloy formation the composition- ∆E diagrams, drawn at a fixed temperature are more informative. As examples EES diagrams are constructed for the liquid Mg-Nd alloy, for some A(III)-B(V) (where A = Al, Ga, In and B = As, Sb), Si-C and for the Al-Ti system. For the Al-rich part of the Al-Ti system, also a semi-schematic non-equilibrium ES diagram is constructed. Based on these diagrams, the synthesis conditions of various phases has been discussed.